الضريبية الجمركية والإصلاح الاقتصادي في مصر - عليوة، زينب توفيق السيد (الجمعية المصرية للاقتصاد السياسي والإحصاء والتشريع, 2009)
The customs policy is related to the economical and social policy in the state and its relationships with the other countries. This policy also affects the individual and the community together. The customs tax is the tax that is imposed on the goods when it passes the boundaries of the state whether going out or going on whether these boundaries are natural or legal boundaries. The amount of the customs tax rises according to the backwardness of the state economy. Where the backward countries tend to consume the imported goods in what push the governments of these countries to impose high customs taxes on importing these goods. And also the easiness of collecting these taxes and the reduction of the spending of obtaining it lead to the heaviness of its outcome. \ On that Hose the r esearch was divided into an introduction and three studies and a conclusion. The first study manipulates the origin of the customs tax in Egypt and the developments of the categories of this tax. And is implemented to increase the tax revenues or for protecting the national product or for fulfilling a definite policy that the state see with the focusing on the customs tax in the light of the program of the economical reform. And also revealing the development of the tax revenues since the beginning of the eighteenth of the nineteenth century and what occurred in it from the variables of its value and its proportion from the sum of the revenues whether the estimated or the real. \ The second study manipulates the economical role of the customs tax in general through the organization of the foreign trade through the effect of this tax on the exports and the imports which achieve three main purposes that are the financial, protectionist and critical purposes and also the effect of the customs tax on the total economical amounts such as the consumption, the savings, investment and production. \ The third study manipulates the customs dealing to the goods of the commercial exchange in Egypt in the light of the economical reform program with the focus on the customs reform. And also the features of the customs tariff of the goods of the commercial exchange through the manifestation of the factors that affect the formation of the tax system. Then the effect of the customs tariff and its proportion from the important economical aggregates such as the gross domestic product and the total revenues and grants and the proportion of the customs tax from the total tax revenues and also its contribution to the spending that the country afford. \ The conclusion of the research contains the important results that were reached in the light of the purpose of research and the hypothesis that the research was based on. One of the important results is that the policy of customs tax has a special importance in the developing countries containing Egypt because of its effective role in achieving the goals of the economical development and correcting the breach in the balance of payments through the first stages of the development. Thus, the success of the customs reform is dependent on the efficiency of the governmental management. Where the policies those are similar on the theoretical level can lead to false re .alts in the practical reaxity. The policies that appear to be efficiently designed cannot succeed within a weak governmental management. Through that the study reached to a group of recommendations that can contribute to the development of the customs tax and the customs management and facing the tax evasion and, thus, achieving the economical goal for its sake the customs tax was imposed.
715676
Keywords: التهرب الضريبي -- مصر -- الاصلاح الاقتصادي -- التنمية الاقتصادية -- الضرائب الجمركية -- الرسوم الجمركية -- الاعفاءات الضريبية -- السياسة الجمركية -- التجارة الخارجية -- التبادل التجاري -- الصادرات -- الواردات -- التعاون الاقتصادي -- التكامل الاقتصادي